Desalination of Seawater to Reduce Ca2+ and Na+ using Natural Zeolite in Vertical Column - Adi Ilcham; Adi Anggara; Anugrah Afzavi Habibilah (Universitas Ahmad Dahlan, 2022)
Water is a source of life. The ocean contains enormous potential for daily life, especially for people who inhabitants near the sea. Around two-thirds of Indonesia’s territory is the ocean. In certain conditions, the seawater has been applied for some industrial processing such as in Gresik Petrochemical. This study aims to reduce the Ca2+ and Na+ content of seawater as part of desalination. In this study, zeolites were supplied from the Wonogiri region. The zeolite rocks were crushed and then sieved to the desired size. The zeolites were washed with distilled water and then dried for 4 hours at 400 oC in the furnace. Furthermore, the zeolites were activated using NaOH solution and heated at 90 oC. After that the zeolite was neutralized and dried within four hours at 110 oC. Furthermore, the zeolite is ready to be applied as adsorbent for separating Ca2+ and Na+. In the experiment, the zeolite is placed in a vertical column pipe and seawater is poured from the bottom of the pipe continuously. After circulating for a certain time, the seawater coming out from the column was analyzed for Ca2+ and Na+ content. Based on observation, it was found that the decreasing of Ca2+and Na+ could reach of 29.75% and 25.14%.